The Effect of Cognitive Behavior Therapy (CBT) to Reduce Generalized Anxiety Disorder (GAD) in Adolescents Based on Gender - Kamil, Nizamuddin; Andik Matulessy; Amanda Pasca Rini (Kirana Publisher (KNPub), 2025)
General Anxiety Disorder (GAD) can occurs in adolescence which can cause uncontrolled feelings of worry about various situations or daily activities. This study aims to examine Generalized Anxiety Disorder (CBT) in reducing GAD based on gender. Respondents in this study were junior high school students at school X. A total of 23 respondents (10 males and 13 females) met the criteria. This study used the one group pretest-posttest design method. The instrument was the Hamilton Anxiety Rating Scale (HARS). The hypothesis test uses Paired Sample T-test with the result p = 0.001 (p <0.05). This shows a significant decrease in anxiety in both male and female adolescents after being given CBT. Based on gender, female adolescents have greater anxiety than males. After being given CBT, both have the same decrease in anxiety.